Effectively Mapping and Charting of Remote Locations with Satellites, Lasers and Acoustics - Cooper, Brad (The International Hydrographic Review, 2021)
In 2018, Toitū Te Whenua Land Information New Zealand (LINZ) commissioned hydrographic survey work in the Ha’apai island group in the Kingdom of Tonga to update the charts in the area to improve maritime safety. A combination of sensor technologies were used in the survey, comprising Satellite Derived Bathymetry (SDB), Airborne Laser Bathymetry (ALB) and Multibeam Echo Sounder (MBES). The novel approach allowed for efficient utilisation of resources during the data acquisition phase. Commencing with SDB, the subsequent ALB extents were refined after a review of the SDB coverage. Similarly, the MBES extents were reviewed based on the achieved ALB coverage. This ensured the efficient and effective use of each technology. Before incorporating the data into charts, each sensor dataset and combinations of datasets were analysed to assess data quality. This informed the decision on how best to portray the data and quality attributes on the charting products.